Stable isotope and organic biomarker analysis of the late Proterozoic Coppercap formation in the MacKenzie Mountains - Thomas, Katherine S., S.M. Massachusetts Institute of Technology (Massachusetts Institute of Technology, 2010)
Thesis: S.B., Massachusetts Institute of Technology, Department of Earth, Atmospheric, and Planetary Sciences, 2010. Cataloged from PDF version of thesis. Includes bibliographical references (unnumbered pages 56-59). Sulfur and carbon stable isotope ratios and organic biomarker abundance were performed on drill core samples from the Coppercap Formation of the Coates Lake Group in the Windermere Supergroup of the MacKenzie Mountains to reconstruct an environmental condition proceeding the first Neoproterozoic Snowball Earth event. The Coppercap Formation directly underlies the Rapitan Group, Sturtian glacigenic deposits, and represents a depositional environment existing directly before the Cryogenian glacial episodes. Based on aryl isoprenoids, n-propyl cholestane, isopropyl cholestane, total organic carbon, carbonate mineral analysis, [delta]34S from pyrite, [delta]13Corganic and [delta]13Ccarbonate values, environmental conditions of the Coppercap Formation were reconstructed. The Coppercap Formation was found to be a shallow euxinic marine basin with purple and green sulfur bacteria microbial mats. This suggest persistent hydrogen sulfide rich waters in the shallow photic zone persisted until the Sturtian. by Katherine S. Thomas. S.B.